Reliability Modelling of a Diesel Engine System Using Fault Tree Analysis Approach - Farhanah Binti Ismail, Farhanah (Universiti Teknologi Petronas, 2010)
The objective of this research was to compute reliability of three diesel engine generator systems at a power plant using Fault Tree Analysis approach. The diesel engine systems had been operated since installed in January 1995 with initial capacity of 8.16 MW. However, their load capacity at the end of December 2009 was 6.0 MW for diesel engine generator sets 1 and 2, while 5.0 MW for set 3. This means that their reliability performance had decreased. The Fault Tree Analysis was used to investigate the causes of decreasing reliability. Fault Tree Analysis was not a common tool for evaluating reliability. To enable the use of Fault Tree Analysis for reliability analysis, the fault tree was converted into Reliability Block Diagram. A power plant was said to be reliability when it has 99.99% performance reliability. The three diesel engine generator systems were evaluated using reliability analysis and compared to the 99.99% of performance. Results of the reliability analysis indicate that two out of three diesel engine generators not meeting the reliability standard. The root cause of this problem was due to sub systems of the diesel engines had high frequency of failure occurrence which led to low reliability